2018
DOI: 10.5688/ajpe6409
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Publication Rates for Abstracts Presented at the American Association of Colleges of Pharmacy Annual Meetings

Abstract: Objectives. Pharmacy education is rapidly changing with an expansion in the number and size of colleges/schools of pharmacy (COP) and increasing expectations for scholarship. However, manuscript publication rates of AACP abstracts is not known. The aim of this study was to examine trends in manuscript publication rates for abstracts presented at the 2000, 2005, 2010, and 2015 AACP annual meetings.Methods. Manuscript publication of AACP abstracts was determined through a systematic search of PubMed, Scopus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
2
8
0
Order By: Relevance
“…Moreover, multicenter RCTs have an evidently higher publication rate, although the number of multicentre RCTs was comparatively limited. Spencer et al also suggested that abstracts with authors from multiple institutions have a comparatively higher publication rate, confirming the findings in this study 28. The cooperation of multiple research institutes may have a positive influence on the study quality and lead to the higher publication rate.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, multicenter RCTs have an evidently higher publication rate, although the number of multicentre RCTs was comparatively limited. Spencer et al also suggested that abstracts with authors from multiple institutions have a comparatively higher publication rate, confirming the findings in this study 28. The cooperation of multiple research institutes may have a positive influence on the study quality and lead to the higher publication rate.…”
Section: Discussionsupporting
confidence: 90%
“…3 Prior studies have found that the full publication rate of abstracts presented at pharmacy meetings is approximately 20%, significantly lower than what has been reported with other health care disciplines. [4][5][6] These previous studies evaluating publication rates at abstracts at pharmacy meetings have not evaluated any one pharmacy specialty. While most peer-reviewed contributions to medical literature are valuable, pharmacists may offer unique insight into the use and optimization of pharmacotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…These studies could be perceived as being more important and thus a better fit for a journal article. Many other studies have confirmed that multi-institutional studies are more likely to get published [ 5 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 89%